Konstruksi Literasi Keagamaan dalam Tafsir The Study Qur’an - Al-Ayyuubi, Mohammad Salahuddin; Haris, Abdul (Contemporary Quran, 2024)
This study investigates how The Study Quran, a commentary led by Seyyed Hossein Nasr, represents religious literacy within the framework of religious and cultural diversity. Employing a qualitative methodology, the research examines this commentary to delineate the concept of religious literacy and illustrates how this concept is manifested in the commentary's interpretation. The findings reveal that "The Study Quran" aims to foster an inclusive discourse by eschewing terminology that could incite sectarian conflict and emphasizing a universal understanding of submission to God. The commentary underscores the significance of interfaith dialogue and diversity while deliberately avoiding extremist interpretations, instead advocating for moderation and justice across various religions. By utilizing a thorough hermeneutical approach and offering a comprehensive understanding of the Quranic teachings, "The Study Quran" emerges as a crucial instrument in promoting peaceful coexistence and mitigating religiously motivated conflicts in multicultural contexts.